Teacher Belief, Knowledge, and Practice: A Trichotomy of Mathematics Teacher Education (Pragyaratna प्रज्ञारत्न, 2024)
This theoretical paper explored and examined three key concepts: the beliefs, knowledge, and practices of math teachers. In order to derive some pedagogical and research implications, I conducted a literature review on teacher beliefs, knowledge, and practices. Three themes emerged from the reviews: teacher beliefs influence practice but in a supportive environment; teacher beliefs influence teacher change (development); and teacher knowledge encompasses more than the whole of content, pedagogical, and technological knowledge and their potential combinations.